Education on the Importance of Elderly Gymnastics to Improve Body Fitness in RW 11 Bentar Hilir Village, Sukamentri, Garut - Nina Sumarni; Udin Rosidin; Umar Sumarna; Iwan Sholahudin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Training that is suitable and safe for the elderly is exercise. The type of exercise that can be done by the elderly is gymnastics, gymnastics for the elderly is a sport that is simple and easy to do. Gymnastics helps maintain physical health, makes bones strong, makes the heart work better and eliminates free radicals in the body. The decline in the musculoskeletal system, especially in the elderly, so exercise such as gymnastics help delay and prevent functional decline in old age. In addition, elderly gymnastics is one of the activities recommended by the Ministry of Health. The purpose of this activity was to provide health education to increase awareness of the importance of elderly gymnastics for body fitness in RW 11 Bentar Hilir Village, Sukamentri, Garut. The method used in this activity was lectures, questions and answers. The result was that, through health education, the elderly understood and knew about the importance of elderly gymnastics to improve body fitness. In conclusion, there is an increase in knowledge about the importance of elderly gymnastics in improving body fitness with 20.2 points.